2012
DOI: 10.1016/j.ijfatigue.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Gigacycle fatigue initiation mechanism in Armco iron

Abstract: a b s t r a c tMicrostructure irreversibility plays a major role in the gigacycle fatigue crack initiation. Surface Persistent Slip Bands (PSB) formation on Copper and its alloy was well studied by Mughrabi et al. as typical fatigue crack nucleation in the very high cycle fatigue regime. In the present paper, Armco iron sheet specimens (1 mm thickness) were tested under ultrasonic frequency fatigue loading in tensioncompression (R = À1). The test on the thin sheets has required a new design of specimen and new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
1
22
0
2
Order By: Relevance
“…On the other hand, the dislocation slips characteristics in polycrystalline copper (fcc) under VHCF conditions have been well studied . Lately, studies for polycrystalline alpha iron (bcc) have been reported . For those two representative polycrystalline metals, the crack initiates from the damaged volume close to the surface where intensive localized irreversible slip bands were found in the interior .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the dislocation slips characteristics in polycrystalline copper (fcc) under VHCF conditions have been well studied . Lately, studies for polycrystalline alpha iron (bcc) have been reported . For those two representative polycrystalline metals, the crack initiates from the damaged volume close to the surface where intensive localized irreversible slip bands were found in the interior .…”
Section: Introductionmentioning
confidence: 99%
“…Дальнейшее развитие и верификация предложенных моделей требуют детального экспериментального исследования процессов развития дефектов в материале на завершающей стадии циклического деформирования с малыми амплитудами. Результаты исследования эволюции структуры армко-железа в [12] показали, что в области гигацикловой усталости в чистом железе могут формироваться как полосы устойчивого сдвига на поверхности образца (аналогично меди или никелю), так и характерные подповерхностные структуры типа «рыбьего глаза».…”
Section: особенности механического поведения армко-железа при испытанииunclassified
“…The study on structural evolution of armco-iron was done in (Wang et al 2012). Here it has been shown that in the region of gigacyclic fatigue, the cyclic deformation of pure iron can lead both to the formation of a stable shear band on the sample surface (by analogy with copper or nickel), and characteristic subsurface structures of the "fish eye" type.…”
Section: Introductionmentioning
confidence: 99%